2015
DOI: 10.1039/c4fo01017e
|View full text |Cite
|
Sign up to set email alerts
|

Stachyose-induced apoptosis of Caco-2 cells via the caspase-dependent mitochondrial pathway

Abstract: Some studies have shown that stachyose, as prebiotics, can prevent indirectly colon cancer cell growth by promoting the proliferation of probiotics or producing beneficial materials in the intestine. However, its direct inhibitory effects on cancer cells are still unclear. Thus, this study aims to investigate the direct inhibitory effect of stachyose on human colon cancer cells and determine the molecular mechanism underlying this effect. The MTT assay was used to assess the inhibitory effect of stachyose on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…* * P < 0:01 vs. the control group. 9 Oxidative Medicine and Cellular Longevity serine/threonine kinase activated by recruitment to the plasma membrane and is a key mediator of PI3K-mediated signal transduction [42,43]. As is shown in Figure 8, the direct results of PI3K phosphorylation is the phosphorylation of AKT, which further affects the expression of Bcl-2 and Bax proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…* * P < 0:01 vs. the control group. 9 Oxidative Medicine and Cellular Longevity serine/threonine kinase activated by recruitment to the plasma membrane and is a key mediator of PI3K-mediated signal transduction [42,43]. As is shown in Figure 8, the direct results of PI3K phosphorylation is the phosphorylation of AKT, which further affects the expression of Bcl-2 and Bax proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PI3K/AKT pathway shows significant antioxidant activity in central and peripheral neurons and can be considered a potential therapeutic target for neurodegenerative diseases, participating in the cellular protective mechanism of ROS-induced cell damage [ 39 ]. AKT is a serine/threonine kinase activated by recruitment to the plasma membrane and is a key mediator of PI3K-mediated signal transduction [ 42 , 43 ]. As is shown in Figure 8 , the direct results of PI3K phosphorylation is the phosphorylation of AKT, which further affects the expression of Bcl-2 and Bax proteins.…”
Section: Discussionmentioning
confidence: 99%
“…When the transmembranous potential of the mitochondria declines, Cyt C located in the space within the mitochondrial membrane is released into the cytoplasm and forms a complex polymer with apoptotic enzyme activators [38] . The protein activates a caspase cascade reaction, which further activates downstream caspase-3 and other members of the caspase family, forming an Apaf-1 and procaspase 9 apoptosis body, and both are further combined with caspase-3 to induce apoptosis [39][40][41] . In this study, we found that the Cyt C protein release and cell apoptosis were increased as the concentration of melittin was elevated ( Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the pro-apoptotic activity of oligosaccharides and low-molecular-weight α-glucans has been described in the literature. Huang et al [4] showed that oligosaccharides (stachyose) induced apoptosis and inhibited the growth of Caco-2 colorectal adenocarcinoma cells. In addition, an oligosaccharide isolated and purified from Bombyx batryticatus was found to induce apoptosis and cell cycle arrest in G 0 /G 1 and G 2 /M phases in HeLa cells [8].…”
Section: Resultsmentioning
confidence: 99%